3D AUGMENTED REALITY SEBAGAI PENDUKUNG BRANDING MUSEUM MPU TANTULAR SIDOARJO - Ardian Jaya Prasetya; Dhika Yuan Yurisma (Jurnal Bahasa Rupa, 2023)
Visitors to the Sidoarjo MPU tantular Museum are dominated by school students who receive assignments from school. Lack of attractions and information in each museum collection causes visitors to be less interested in visiting. The main objective of this research is to designing three-dimensional Augmented reality design as an effort to brand the mpu tantular museum in Sidoarjo. By using Augmented reality technology, visitors can interact directly with museum collections. The method used in this study is the Multimedia Development Life Cycle with a direct approach by observation and interviews. From the results of data analysis, it was found that the concept of augmented reality was used, namely in the form of an Instagram application filter so that visitors would immediately share their experiences visiting the mpu tantular museum on their social media and be able to communicate to the public. The media implementation uses a 5x5 cm sticker affixed near the selected collection as a marker, visitors only need to scan the marker.